Answered

Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Consider the function [tex]f(x)=2x^3-3x^2-72x+9[/tex] on the interval [tex][-4, 8][/tex].

1. Find the average or mean slope of the function on this interval.
2. By the Mean Value Theorem, we know there exists a [tex]c[/tex] in the open interval [tex](-4, 8)[/tex] such that [tex]f^{\prime}(c)[/tex] is equal to this mean slope. For this problem, there are two values of [tex]c[/tex] that work.

The smaller one is [tex]\square[/tex] and the larger one is [tex]\square[/tex].


Sagot :

To solve this problem, we'll follow a structured approach to find the mean slope of the function [tex]\( f(x) = 2x^3 - 3x^2 - 72x + 9 \)[/tex] on the interval [tex]\([-4, 8]\)[/tex] and identify the values of [tex]\( c \)[/tex] in this interval that satisfy the conditions of the Mean Value Theorem (MVT).

### Step 1: Calculate the Mean Slope

The mean slope of the function on the interval [tex]\([a, b]\)[/tex] is given by:
[tex]\[ \text{Mean Slope} = \frac{f(b) - f(a)}{b - a} \][/tex]

For our function [tex]\( f(x) \)[/tex], we have [tex]\( a = -4 \)[/tex] and [tex]\( b = 8 \)[/tex]. We need to find [tex]\( f(a) \)[/tex] and [tex]\( f(b) \)[/tex]:

1. Evaluate [tex]\( f(-4) \)[/tex]:
[tex]\[ f(-4) = 2(-4)^3 - 3(-4)^2 - 72(-4) + 9 = 2(-64) - 3(16) + 288 + 9 = -128 - 48 + 288 + 9 = 121 \][/tex]

2. Evaluate [tex]\( f(8) \)[/tex]:
[tex]\[ f(8) = 2(8)^3 - 3(8)^2 - 72(8) + 9 = 2(512) - 3(64) - 576 + 9 = 1024 - 192 - 576 + 9 = 265 \][/tex]

Now, compute the mean slope:
[tex]\[ \text{Mean Slope} = \frac{f(8) - f(-4)}{8 - (-4)} = \frac{265 - 121}{8 + 4} = \frac{144}{12} = 12 \][/tex]

### Step 2: Apply the Mean Value Theorem (MVT)

The MVT states that if [tex]\( f \)[/tex] is continuous on [tex]\([a, b]\)[/tex] and differentiable on [tex]\((a, b)\)[/tex], then there exists a [tex]\( c \)[/tex] in [tex]\((a, b)\)[/tex] such that:
[tex]\[ f'(c) = \text{Mean Slope} \][/tex]

### Step 3: Find [tex]\( f'(x) \)[/tex] and Solve for [tex]\( c \)[/tex]

First, find the derivative of [tex]\( f(x) \)[/tex]:
[tex]\[ f'(x) = \frac{d}{dx} (2x^3 - 3x^2 - 72x + 9) = 6x^2 - 6x - 72 \][/tex]

We need to find the values of [tex]\( c \)[/tex] in [tex]\((-4, 8)\)[/tex] such that [tex]\( f'(c) = 12 \)[/tex]:

Solve the equation:
[tex]\[ 6c^2 - 6c - 72 = 12 \][/tex]

First, simplify:
[tex]\[ 6c^2 - 6c - 72 - 12 = 0 \][/tex]
[tex]\[ 6c^2 - 6c - 84 = 0 \][/tex]
[tex]\[ c^2 - c - 14 = 0 \][/tex]

Solve the quadratic equation [tex]\( c^2 - c - 14 = 0 \)[/tex] using the quadratic formula [tex]\( c = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex] where [tex]\( a = 1 \)[/tex], [tex]\( b = -1 \)[/tex], and [tex]\( c = -14 \)[/tex]:

[tex]\[ c = \frac{-(-1) \pm \sqrt{(-1)^2 - 4(1)(-14)}}{2(1)} = \frac{1 \pm \sqrt{1 + 56}}{2} = \frac{1 \pm \sqrt{57}}{2} \][/tex]

The solutions are:
[tex]\[ c = \frac{1 + \sqrt{57}}{2} \quad \text{and} \quad c = \frac{1 - \sqrt{57}}{2} \][/tex]

### Final Step: Determine Numerical Values

By evaluating expressions, we find:
The smaller value is:
[tex]\[ \frac{1 - \sqrt{57}}{2} \approx -3.2749 \][/tex]

The larger value is:
[tex]\[ \frac{1 + \sqrt{57}}{2} \approx 4.2749 \][/tex]

### Conclusion

The smaller value of [tex]\( c \)[/tex] is approximately [tex]\(-3.2749\)[/tex] and the larger value of [tex]\( c \)[/tex] is approximately [tex]\(4.2749\)[/tex]. Therefore,

The smaller one is [tex]\(-3.2749\)[/tex] and the larger one is [tex]\(4.2749\)[/tex].